2020
DOI: 10.3389/fnhum.2020.589634
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Contrast Adaptation Does Not Cause Habituation of the Adapter

Abstract: Adaptation can optimize information processing by allowing the visual system to always adjust to the environment. However, only a few studies have investigated how the visual system makes adjustments to repeatedly occurring changes in the input, still less about the related neural mechanism. Our previous study found that contrast adaptation attenuated after multiple daily sessions of repeated adaptation, which was explained by the habituation of either the adapter’s effective strength or the adaptation mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…To focus on the electrodes with sufficiently strong responses, for each electrode we compared the average SSVEP amplitude for both eyes in the pre- and post-tests with the grand mean amplitude across all the electrodes and subjects by using a one-sample t -test ( Huang et al. 2018 ; Dong et al. 2020 ; Lyu et al.…”
Section: Methodsmentioning
confidence: 99%
“…To focus on the electrodes with sufficiently strong responses, for each electrode we compared the average SSVEP amplitude for both eyes in the pre- and post-tests with the grand mean amplitude across all the electrodes and subjects by using a one-sample t -test ( Huang et al. 2018 ; Dong et al. 2020 ; Lyu et al.…”
Section: Methodsmentioning
confidence: 99%
“…20 If they do, then perceptual responses after repeated episodes of short-term MD should wane over time in line with what is known about contrast adaptation. [21][22][23] As previously mentioned, similarities are their dynamics from single sessions and the fact that they both involve the removal of contrast to one eye. Also, there are some differences between the two phenomena.…”
Section: Discussionmentioning
confidence: 88%
“…[21][22][23][24][25][26] Previous studies reported that perceptual deterioration is observed when six to eight (but not more) repetitions of adaptation are introduced in a cluster. 21,[27][28][29] If perceptual deterioration is also present in the effect of short-term MD, its effect too should decrease after repeated periods of short-term MD, supporting that both contrast adaptation and the effect of short-term MD could share the same neural basis. In addition, if shortterm MD is incorporated in clinical settings for adults with impaired binocular vision, it will be preferable if each session of short-term MD induces a maximal effect because the treatment protocol can involve consecutive periods of short-term MD across weeks or months and be more likely to restore long-term eye balance.…”
Section: O R I G I N a L A R T I C L E Daily Dose-response From Short...mentioning
confidence: 99%
See 2 more Smart Citations